2005
DOI: 10.1111/j.1523-1755.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study for prevention of postrenal transplantation bone loss

Abstract: This study proves that early bone loss that occurs during the first 12 months after renal transplantation could be prevented by alfacalcidol, calcitonin, or alendronate. Among the treatment groups, alfacalcidol significantly improved the hyperparathyroidism. All treatment drugs are safe and tolerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 26 publications
0
72
0
4
Order By: Relevance
“…El-Agroudy et al (66), in another study with 40 male patients who were randomly assigned to ␣-calcidiol plus calcium or placebo, demonstrated that the bone loss that occurred during the first year after renal transplantation could be prevented by ␣-calcidiol. This same group in a recent report randomly assigned 60 adult male patients to placebo, ␣-calcidiol, oral alendronate, or intranasal salmon calcitonin and showed that all treatment groups demonstrated improvement in BMD at all sites, with decreased BMD in the control group (67).…”
Section: Use Of Vitamin D Metabolitesmentioning
confidence: 99%
“…El-Agroudy et al (66), in another study with 40 male patients who were randomly assigned to ␣-calcidiol plus calcium or placebo, demonstrated that the bone loss that occurred during the first year after renal transplantation could be prevented by ␣-calcidiol. This same group in a recent report randomly assigned 60 adult male patients to placebo, ␣-calcidiol, oral alendronate, or intranasal salmon calcitonin and showed that all treatment groups demonstrated improvement in BMD at all sites, with decreased BMD in the control group (67).…”
Section: Use Of Vitamin D Metabolitesmentioning
confidence: 99%
“…One report noted that intranasal salmon calcitonin 200 IU every other day can prevent early bone loss as effectively as alendronate and alfacalcidol [57] . But other studies failed to demonstrate its superiority to calcium supplementation in transplant recipients [58,59] .…”
Section: Calcitoninmentioning
confidence: 99%
“…One report noted that intranasal salmon calcitonin 200 IU every other day can prevent early bone loss as effectively as alendronate and alfacalcidol in renal transplant recipients (El-Agroudy et al, 2005). But other studies have failed to demonstrate superiority to calcium supplementation in transplant recipients (Bone et al, 2004;Palmer et al, 2005;.…”
Section: Calcitoninmentioning
confidence: 99%